Eucoleus boehmi infection in a dog with high parasitic burdens - Fariña, Fernando Adrian (2021)
Eucoleus boehmi (syn. Capillaria boehmi) is a trichurid nematode parasite of the upper respiratory tract in canids with a generally asymptomatic course. It is presented the clinical case of a 9-year-old mestizo male canine from the province of Buenos Aires, Argentina, who had previously been treated for eucoleosis, presenting cough, sneezing, reverse sneezing, abundant bilateral serous nasal discharge. The analysis of faecal samples was performed by the Bembrook and McMaster techniques, revealing the presence of 10 900 epg of E. boehmi. Treatment and monitoring of the patient was performed until complete remission of clinical signs and the absence of eggs in the stool.